THE EFFECT OF COMMISSION AGENT, CLIMATE AND PROFIT MARGIN ON SWEET ORANGE SALES KUTABULUH GUGUNG VILLAGE, KARO REGENCY - Desy Ramadani; Hasrul Azwar Hasibuan; Dewi Kumala Sari; Dwi Nur Fadilla (Universitas Efarina, 2021)
The purpose of this study was to determine whether commission agents, climate and profit margins partially and simultaneously have a positive and significant effect on sweet orange sales in Kutabuluh Gugung Village, Kutabuluh District, Karo Regency. The analysis methods used are quantitative methods and multiple linear regression analysis. The data used in this study are primary data. The data collection methods in this study were interview studies and questionnaires. This study used 50 respondents as samples in the study and the sampling method used saturated samples. The results showed that commission agents, climate and profit margins partially and simultaneously had a positive and significant effect on sweet orange sales in Kutabuluh Gugung Village, Kutabuluh District, Karo Regency.